Nigeria zero hunger/IITA policy brief No. 2: Nigeria zero hunger strategic review-nutritional status of children under the age of 5 in Ebonyi state, Nigeria - Okike, Iheanacho; Ayoola, G.B.; Ogundapo, A.T.; Ojide, M.; Abdoulaye, Tahirou; Dashiell, Kenton E.; Manyong, Victor (Herald Scholarly Open Access, 2021)
The Federal Republic of Nigeria committed to achieving the “2030 Agenda for Sustainable Development” (also known as Sustainable Development Goals - SDGs).